GMS-SCRN: A gated multi-scale Swin Transformer network with local orthogonality for seismic data denoising - Mengjun Cao; Jianping Huang; Chao Ma; Zixuan Qiao; Jintao Liu; Yan Huang (Journal of Applied Geophysics, 2026)

Prenatal parabens exposure and infantile Eczema: Mediation by IL-17A, effect modification by breastfeeding, and evidence from network toxicology - Mengjun Chang; Xianjia Li; Ye Li; Yueyi Lv; Jin Ji; Can Liu; Guoai Yu; Xingyu Liao; Jie Gao; Leina Jia; Suzhen Guan (Environmental Pollution, 2026)

Rational Ba doping induces multiphase architecture in PrNi0.5Co0.5O3-δ for enhanced triple conductivity in protonic ceramic electrochemical cells - Mengjun Tang; Xiao Zhang; Waqas Muhammad; Yinghua Niu; Sheng Ma; Zuorui Xin; Jiaqi Wang; Tingting Liu; Mian Li; Liping Dai; Jinquan Wang; Zihao Xu; et al. (Chemical Engineering Journal, 2026)

Improving real-time PPP time transfer with the augmentation of predicted tropospheric products - Wei Xie; Kan Wang; Mengyuan Li; Zi Chen; Guolin Liu; Mengjun Wu; Xiaolong Mi; Xuhai Yang (GPS Solutions, 2026)
Real-time precise point positioning (PPP) time transfer is a crucial technique for the time and frequency field. However, its performance remains limited by the relatively long convergence time resulting from unstable parameter estimation in the initial stage. In this contribution, predicted tropospheric products provided by the Global Forecast System (GFS) are employed to derive predicted Zenith Wet Delays (ZWDs) for each station. The predicted ZWDs are subsequently incorporated into the real-time PPP as virtual observations, thereby enhancing the performance of the real-time PPP time transfer. One week of data from 20 globally distributed stations was used to form 19 time links. Results showed that the average root mean square error (RMSE) for the predicted ZWD amounts to 1.4 cm. For the traditional PPP strategy with ZWD estimation, the average convergence time of all links is 7.18 and 9.24 min for the static and kinematic modes, respectively. With the ZWD augmentation, they are shortened to 5.77 and 7.26 min, with improvements of 19.6% and 21.4%, respectively. In terms of the time link precision, the traditional and GFS ZWD-augmented methods yield 0.483 and 0.414 ns in the static mode, and 0.607 and 0.508 ns in the kinematic mode, with improvements of 14.3% and 16.3%, respectively. Regarding time link stability, improvements range from 10.0 to 20.6% in the static mode and from 9.7 to 21.4% in the kinematic mode when the averaging time is from 30 to 3600 s. These results clearly demonstrate that incorporating ZWD as external constraints can significantly enhance real-time PPP time transfer, particularly during the convergence period.

Cooperative microorganisms in nitrification-denitrification sludge as the hidden helper for rapid anammox enrichment - Yongen Dong; Guanqi Wu; Ying Xu; Mengjun Yuan; Xiyue Zhang; Naif Abdullah Al-Dhabi; Lanhua Liu; Bo Shen; Baodan Jin; Wangwang Tang; Jiantao Ji (Environmental Research, 2026)

A design-stage surrogate-assisted optimization framework for ship structural vibration reduction using reduced-order and Bayesian calibration models - Dakuan Xin; Juxi Hu; Mengjun Xie; Siyuan Liu (Ocean Engineering, 2026)

Hydrodesulfurization catalysts for ultra-clean diesel: Recent progress, modulation strategies, and emerging alternatives - Haihong Zhang; Chongchong Wu; Huiling Zhang; Ning Wang; Yu Song; Longnian Han; Siran Zhang; Mengjun Su; Jian Liu; Zhanggui Hou (Fuel, 2026)

Interface-driven WO3-ZnO-g-C3N4 nanoheterostructures for electrochemical monitoring of trimethoprim and visible-light photocatalytic remediation of organic pollutants - Weiping Liu; Zhu Wu; Mengjun Zeng; Shanting Tang; Meihua Bao (Environmental Geochemistry and Health, 2026)

Study on the electrocatalytic reduction mechanism of PFOA degradation at gradient sulfur-doped copper sites - Hailong Wang; Ruijie Ge; Chenjian Ye; Jianzhong Zhu; Jue Liu; Liang Chen; Mengjun Xu; Jianbo Ma (Environmental Research, 2026)

Gibberellin delays the red-turning of jujube fruit during storage via browning inhibition: Insights from targeted metabolomics - Tianyu Li; Jiaqi Liu; Jialin Tao; Tong Wu; Mengjun Liu; Shoukun Han (Postharvest Biology and Technology, 2026)

Rapid grouting evaluation with magnetic detection: Methods and mechanisms - Botao Wang; Jiacheng Zhang; Luoluo Song; Zhiheng Wang; Rentai Liu; Xiuhao Li; Shihao Luo; Mengjun Chen; Jiwen Bai (Journal of Applied Geophysics, 2026)

Design of structurally enhanced dual-network high internal phase emulsion gels for 3D-printable plant-based fat substitutes using carboxymethyl cellulose/heat-treated soy protein isolate and k-carrageenan - Yifei Liu; Yu Xia; Yiqiang Dai; Mengjun Sun; Xiudong Xia; Mingsheng Dong (Food Chemistry, 2026)

Sensory-metabolomics insights into quality alteration of dried jujube (Ziziphus jujuba ‘Huizao’) fruit in prolonged storage - Ye Yuan; Lili Li; Jiamin Li; Xiaojuan Yang; Shoule Wang; Bingqi Shen; Chong Chen; Juan Jin; Lei Yang; Dingyu Fan; Mengjun Liu; Zhihui Zhao; et al. (Food Chemistry, 2026)

Differential accumulation of triterpenoids in Ziziphus jujuba and Ziziphus acidojujuba: insights from terpenoid metabolomics across organs and developmental stages - Fuxu Pan; Yufei Song; Tianshuo Jia; Zhiguo Liu; Xianwei Meng; Zhihui Zhao; Mengjun Liu; Lili Wang (Food Chemistry, 2025)

Core-shell structure and twin-cone morphology of Au@Ag@HOF with efficient adsorption capability and high SERS enhancement efficiency for sensitive detection of bisphenol compounds in food - Xiaoyu Yang; Shunbi Xie; Weifen Wu; Jingwen Liu; Manjun Liao; Runzi Zhang; Yao Liu; Mengjun Wang; Yi He (Food Chemistry, 2025)

Inulin and metal-phenolic network single-cell encapsulation: Boosting the tolerance and intestinal colonization capability of Bifidobacterium lactis - Mengjun Wang; Shuo Zhang; Siyan Liu; Linyu Nian; Suilou Wang; Chongjiang Cao (Food Hydrocolloids, 2025)

Effects of Zygosaccharomyces rouxii on metabolites and volatile substances during the fermentation of jujube beverage based on LC-MS, HS-GC-IMS and ET analysis - Peixing Ren; Xiaojing Zheng; Ruirui Dao; Jia Tian; Shuang Wu; Hanbing Zhu; Lili Wang; Mengjun Liu; Zhihui Zhao (Food Chemistry, 2025)

Two-dimensional surface induced strategy enabling high-quality halide perovskite thin film growth via vapor-solid reactions - Meichen Liu; Shenghan Hu; Changyu Duan; Xinyu Deng; Yichen Dou; Mengjun Liu; Yuanbo Song; Tiancan Zhang; Guijie Liang; Zhiliang Ku (Chemical Engineering Journal, 2025)

Sodium alginate/carboxymethyl chitosan/gelatin-naringenin pH-responsive hydrogel beads for oral delivery of traditional Chinese herbal medicines - Zixing Yan; Qingling Nie; Jiajia Liu; Jingxin Chen; Youmei Liu; Yudong Lu; Mengjun Xu; Zhenwen Lin (Carbohydrate Polymers, 2025)

Dual-catalytic hairpin amplification strategy as a highly efficient signal amplifier cooperative with COF@Au for ultrasensitive SERS detection of miRNA-21 - Runzi Zhang; Shunbi Xie; Youlin Tang; Xiang He; Xiaoyu Yang; Yao Liu; Mengjun Wang; Yi He (Analytica Chimica Acta, 2025)

Effects of co-exposure to microplastics and perfluorooctanoic acid on the Caco-2 cells - Xingyu Zou; Mengjun Pan; Yue Liu; Shuai Wang; Hongye Xu; Xiaoqin Chu (Toxicology, 2025)

Gibberellin and shikimic acid enhance ascorbic acid accumulation and ROS scavenging ability to delay the senescence of postharvest jujube fruit - Kangning Jiang; Xiaohuan Zhang; Tianyu Li; Jiaqi Liu; Mengjun Liu; Shoukun Han (Postharvest Biology and Technology, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

The Collaborative Role of the Regulatory (MYB-bHLH-WD40) and Structural Genes Results in Fruit Coloration in Plants Some Do This Under the Influence of External Stimuli - Noor Muhammad; Zhi Luo; Zhiguo Liu; Mengjun Liu (Journal of Plant Growth Regulation, 2025)

Genome and transcriptome-based characterization of cytochrome P450 (CYP) monooxygenase superfamily gene and the key role of ZjCYP98A9a-89 in flavonoid biosynthesis during fruit development of jujube (Ziziphus jujuba Mill.) - Noor Muhammad; Yao Liu; Zhiguo Liu; Lixin Wang; Minsheng Yang; Mengjun Liu (Food Bioscience, 2025)

Regulation of skin pigments in winter jujube fruit treated with elevated O2 - Dong Li; Wenxuan Li; Qingqing Wang; Yanpei Chen; Yanqun Xu; Xingtao Zhang; Zhihui Zhao; Mengjun Liu; Qinyang Cheng; Zisheng Luo (Postharvest Biology and Technology, 2024)

Fire alters soil bacterial and fungal communities and intensifies seasonal variation in subtropical forest ecosystem - Ziyue Shi; Yaru Chen; Aogui Li; Mengjun Hu; Weixing Liu (European Journal of Soil Biology, 2024)

A novel fluorescence immunoassay for the quantitative detection of florfenicol in animal-derived foods based on ZnCdSe/ZnS quantum dot labelled antibody - Cheng Xin; Jingming Zhou; Yumei Chen; Yankai Liu; Hongliang Liu; Chao Liang; Xifang Zhu; Ying Zhang; Zhuting Chen; Xueyuan Tang; Bingxue Zhang; Mengjun Lu; et al. (Food Chemistry, 2024)

A novel coupled algorithm for Studying the performance characteristics of water ramjet in the flight of supercavitating vehicle - Yanxi Yang; Mengjun Wang; Junpeng Liu; Pingan Liu; Lu Wang (Ocean Engineering, 2024)

The underlying molecular mechanisms of hormonal regulation of fruit color in fruit-bearing plants - Noor Muhammad; Zhiguo Liu; Lixin Wang; Minsheng Yang; Mengjun Liu (Plant Molecular Biology, 2024)

Analysis of binding and authentic virus-neutralizing activities of immune sera induced by various monkeypox virus antigens - Shuo Song; Zuning Ren; Jiayin Chen; Mengjun Li; Yushan Jiang; Yingxia Liu; Bao Zhang; Hongzhou Lu; Wei Zhao; Chenguang Shen; Yang Yang (Immunologic Research, 2024)

Taxonomic turnover dominates changes in soil microbial communities and functions in response to wildfire in subtropical forest - Ziyue Shi; Yaru Chen; Aogui Li; Chao Wang; Mengjun Hu; Weixing Liu (Applied Soil Ecology, 2024)

Changes in soil bacterial community diversity and its network stability under different grazing intensities in plateau rangelands - Mengjun Liu; Qing Yang; Bingjie Yan; Yue Ren; Xiaodong Li; Shiying Zhu; Migmar Wangdwei (Agriculture, Ecosystems & Environment, 2024)

Coordinated responses of rice (Oryza sativa) to the stresses of benzotriazole ultraviolet stabilizers (BZT-UVs): Antioxidative system, photosynthetic activity, and metabolic regulation - Huijun Liu; Mengjun Wang; Siyuan Jin; Qian Guo; Shuping Wang; Haohua Ni; Hainan Lu; Zhiheng Li (Journal of Hazardous Materials, 2024)

Cropland inundation mapping in a mountain dominated region based on multi-resolution remotely sensed imagery and active learning for semantic segmentation - Hao Jiang; Jianhui Xu; Xun Zhang; Xia Zhou; Yangxiaoyue Liu; Mengjun Ku; Kai Jia; Xuemei Dai; Yishan Sun; Shuisen Chen (Journal of Hydrology, 2024)

Nanotechnology-based optical sensors for Baijiu quality and safety control - Wei Dong; Zhen Fan; Xiaolong Shang; Mengjun Han; Baoguo Sun; Caihong Shen; Miao Liu; Feng Lin; Xiaotao Sun; Yanfei Xiong; Bo Deng (Food Chemistry, 2024)

c-Jun targets miR-451a to regulate HQ-induced inhibition of erythroid differentiation via the BATF/SETD5/ARHGEF3 axis - Yanrong Lv; Xiaoju Ma; Qing Liu; Zihao Long; Shuangqi Li; Zhaoqing Tan; Dongsheng Wang; Xiumei Xing; Liping Chen; Wen Chen; Qing Wang; Qing Wei; et al. (Toxicology, 2024)

Electrolytic manganese residue pretreated by filter press-water washing and carbide slag: Manganese recycling, depth harmless and dispersion - Dejun He; Mengjun Chen; Hui Liu (Process Safety and Environmental Protection, 2024)

Experimental investigation of high-temperature water vapour ventilated supercavitation - Yanxi Yang; Lu Wang; Hao Chang; Pingan Liu; Mengjun Wang (Ocean Engineering, 2024)

Multiomics integrated with sensory evaluations to identify characteristic aromas and key genes in a novel brown navel orange (Citrus sinensis) - Zhehui Hu; Mengjun Chen; Kaijie Zhu; Yuan Liu; Huan Wen; Jiatao Kong; Minghua Chen; Lixin Cao; Junli Ye; Hongyan Zhang; Xiuxin Deng; Jiajing Chen; et al. (Food Chemistry, 2024)

Empirical analysis of lead neurotoxicity mode of action and its application in health risk assessment - Hehai Huang; Yanrong Lv; Qingfei Chen; Xiaowei Huang; Jingyao Qin; Yan Liu; Qilong Liao; Xiumei Xing; Liping Chen; Qing Liu; Shuangqi Li; Zihao Long; et al. (Environmental Research, 2024)

Preparation of anti-washout cement-stabilized marine soft clay for scouring protection of wind power pile foundations - Xiuhao Li; Zhijing Zhu; Rentai Liu; Chunyu Zhang; Qingsong Zhang; Shucai Li; Mengjun Chen (Marine Georesources & Geotechnology, 2024)

Unlocking the secrets of Qingzhuan tea: A comprehensive overview of processing, flavor characteristics, and health benefits - Panpan Liu; Lin Feng; Jia Chen; Shengpeng Wang; Xueping Wang; Yanna Han; Mengjun Ma; Zhonghua Liu; Pengcheng Zheng (Trends in Food Science & Technology, 2024)

Preparation, characterization and in vitro digestion of jujube polysaccharide microcapsules - Qingyi Li; Meiling Liu; Mengjun Liu; Huiqiang Wang; Zhihui Zhao (Food and Bioproducts Processing, 2024)

8-OHdG mediates the association of co-exposure to fifty-five typical endocrine-disrupting chemicals with renal function: a cross-section investigation in Southern Chinese adults - Qingfei Chen; Qifei Deng; Qilong Liao; Yan Liu; Zhaorui Zhang; Dehua Wu; Yanrong Lv; Jingyao Qin; Qing Liu; Shuangqi Li; Zihao Long; Xiumei Xing; et al. (Environmental Science and Pollution Research, 2024)

Photoaged microplastics enhanced the antibiotic resistance dissemination in WWTPs by altering the adsorption behavior of antibiotic resistance plasmids - Qian Guo; Mengjun Wang; Siyuan Jin; Haohua Ni; Shuping Wang; Jie Chen; Wenlu Zhao; Zhiguo Fang; Zhiheng Li; Huijun Liu (Science of The Total Environment, 2024)

Predicting Drug-Drug Interactions Involving Rifampicin Using a Semi-mechanistic Hepatic Compartmental Model - Jingxi Li; Xue Li; Keheng Wu; Sihui Long; Youni Zhao; Xiong Jin; Mengjun Zhang; Xinyi Wu; Zhijun Huang; Zhou Zhou; Jack Liu; Bo Liu (Pharmaceutical Research, 2024)

Spatiotemporal characteristics of evaporation in China and its response to revegetation in a typical region by a generalized complementary approach - Haixiang Zhou; Changwu Cheng; Mengjun Hu; Wenzhao Liu; Bo Zhang (Agricultural and Forest Meteorology, 2023)

Treatment of Water Inrush in Mine Engineering Using a Superabsorbent Polymer: A Case Study of a Limestone Mine, Pingnan, China - Chenyang Ma; Yu’an Gong; Mengjun Chen; Rentai Liu; Jiwen Bai; Zhuo Zheng; Mengmeng Zhou (Mine Water and the Environment, 2023)

Effects of decreased precipitation and thinning on soil respiration in a temperate forest: A one-year field experiment in Central China - Jiali Wang; Hao Liu; Mengjun Hu; Yue Du; Yanchun Liu; Longlong Lu; Shijie Han (CATENA, 2023)

Evolution of silicate weathering in South China since 30 Ma: Controlling factors and global implications - Hualong Jin; Shiming Wan; Chang Liu; Debo Zhao; Wenqiang Pei; Zhaojie Yu; Jin Zhang; Zehua Song; Mengjun Li; Yi Tang; Anchun Li (Global and Planetary Change, 2023)

Solid-liquid interface adsorption of antibiotic resistance plasmids induced by nanoplastics aggravates gene pollution in aquatic ecosystems - Zhiheng Li; Mengjun Wang; Hong Fang; Zhangchao Yao; Huijun Liu; Wenlu Zhao; Jie Chen (Environmental Pollution, 2023)

Genomic constitution and relationships of Ziziphus species collected from Malakand Division, Pakistan - Nisar Uddin; Noor Muhammad; Niaz Ali; Mohammad Nisar; Mengjun Liu (Physiology and Molecular Biology of Plants, 2022)

Radium isotope assessment of submarine groundwater discharge and associated nutrient inputs in Eastern Liaodong Bay, China - Qiaona Guo; Yue Zhao; Mengjun Li; Jinhui Liu (Frontiers in Marine Science, 2022)
The accurate assessment of submarine groundwater discharge (SGD) and associated nutrient fluxes plays a significant role in water resources management and ecological environment protection in the coastal area. Currently, Liaodong Bay has become one of the most polluted marine areas in China. However, the nutrient fluxes carried by the SGD and its environmental effects have not yet been thoroughly reported in eastern Liaodong Bay, China. In this study, the distribution of 224 Ra/ 223 Ra activity ratio and its influencing factors under the geochemical conditions were explored. The activity of radium was affected by the water type and the geochemical factors. The radium isotopes in seawater were positively correlated with the ratios of Mg 2+ /Na + and Ca 2+ /Na + but negatively correlated with salinity and SO 4 2− . The average apparent water age was evaluated to be 13.0 days. Furthermore, based on the radium mass balance model, the total average SGD flux was calculated to be 1.31 × 10 8 m 3 day –1 . The nutrient fluxes carried by the SGD were 7.16 × 10 7 , 1.01 × 10 6 , 1.61 × 10 7 , 0.92 × 10 6 , and 5.41 × 10 7 mol day −1 for DIN, DIP, NH 4 + , NO 2 − , and NO 3 − , respectively. The nutrient inputs through the SGD have an average DIN : DIP ratio of 70, which was able to seriously affect the ecological environment. The SGD-derived nutrient fluxes were higher than the local river input, which demonstrated that the SGD was a major source of nutrients affecting regional marine ecosystems.

Evaluation of a Superabsorbent Polymer for Plugging Karst Pipe Type Water Inrushes - Chenyang Ma; Shucai Li; Rentai Liu; Yan Pei; Chunyu Zhang; Yankai Liu; Fei Xu; Xiao Feng; Mengjun Chen (Mine Water and the Environment, 2022)

SSR-based population structure, molecular diversity and identity cards of Ziziphus species from Pakistan and China - Nisar Uddin; Niaz Ali; Mohammad Nisar; Mengjun Liu; Zhiguo Liu; Noor Muhammad; Inayat Ur Rahman (Genetic Resources and Crop Evolution, 2021)

Spatiotemporal pattern analysis of potential light seine fishing areas in the East China sea using VIIRS day/night band imagery - Lingwei Luo; Mengjun Kang; Jinhui Guo; Ying Zhuang; Zebin Liu; Yameng Wang; Liping Zou (International Journal of Remote Sensing, 2019)

Sophocarpine attenuates murine lupus nephritis via inhibiting NLRP3 inflammasome and NF-κB activation - Xiuzhen Li; Mengjun Wang; Hong Hong; Congjuan Luo; Zewei Liu; Ruiheng Yang (Immunologic Research, 2018)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

16S rDNA sequence analysis of witches’ broom phytoplasma isolates from Chinese jujube in North China - Jiaodi Bu; Long Peng; Mengjun Liu; Jin Zhao (Australasian Plant Pathology, 2016)

Association of obesity and overweight with overall survival in colorectal cancer patients: a meta-analysis of 29 studies - Shuangjie Wu; Jun Liu; Xinhai Wang; Mengjun Li; Yu Gan; Yifan Tang (Cancer Causes & Control, 2014)

Cloning and expression of a tau class glutathione S-transferase (ZjGSTU1) from Chinese jujube in response to phytoplasma infection - Long Peng; Yanlin Zhao; Zhihui Zhao; Jin Zhao; Mengjun Liu (Acta Physiologiae Plantarum, 2014)

Reverse-cleft in vitro micrografting of Ziziphus jujuba Mill. Infected with jujube witches’ broom (JWB) - Xiaoguang Liu; Mengjun Liu; Qiang Ning; Guannan Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Cytological mechanism of 2n pollen formation in Chinese jujube (Ziziphus jujuba Mill. ‘Linglingzao’) - Zhihui Xue; Ping Liu; Mengjun Liu (Euphytica, 2011)